Ductus Arteriosus Aneurysm and Pulmonary Artery Thromboses in a Protein S-Deficient Newborn - Shirozu, Hiromitsu; Ichiyama, Masako; Ishimura, Masataka; Ayako, Kuraoka; Egami, Naoki; Dongchon, Kang; Nakano, Toshihide; Sagawa, Koichi; Ohga, Shouichi (American Journal of Perinatology Reports, 2023)
Ductus arteriosus aneurysm (DAA) asymptomatically occurs in newborn infants and resolves spontaneously. High-risk DAA with compression, rupture, and thrombosis requires early surgical intervention. Newborn infants have the highest risk of thrombosis among pediatric patients, but the genetic predisposition is difficult to determine in infancy. We herein report a neonatal case of massive thromboses in DAA and pulmonary artery. Desaturation occurred in an active full-term infant 2 days after birth. Echocardiography and contrast-enhanced computed tomography indicated thrombotic occlusion of the DAA and pulmonary artery thrombus. Urgent thrombectomy and ductus resection were successfully performed. After 6 months of anticoagulant therapy, the dissociated low plasma activity levels of protein S from protein C suggested protein S deficiency. A genetic study of PROS1 identified a heterozygous variant of protein S K196E, a low-risk variant of thrombophilia in Japanese populations. There have been seven reported cases with neonatal-onset symptomatic thromboses of DAA involving the pulmonary artery. All survived without recurrence after surgical intervention in five and anticoagulant therapy alone in two. Two newborns had a heterozygous methylenetetrahydrofolate reductase (MTHFR) variant, but information on thrombophilia was not available for any other cases. A genetic predisposition may raise the risk of DAA thrombosis, leading to rapid progression.
Keywords: ductus arteriosus aneurysm; thrombophilia; protein S deficiency; K196E